Impacting the Treatment of Highly Eloquent Supratentorial Cerebral Cavernous Malformations by Noninvasive Functional Mapping—An Observational Cohort Study. Issue 6 (8th October 2021) - Ille, Sebastian; Schroeder, Axel; Hostettler, Isabel C; Wostrack, Maria; Meyer, Bernhard; Krieg, Sandro M
Abstract: BACKGROUND: Cerebral cavernous malformations (CCM) may cause cavernoma-related epilepsy (CRE) and intracranial hemorrhage (ICH). Functional mapping has shown its usefulness during the resection of eloquent lesions including the treatment of brain arteriovenous malformations. OBJECTIVE: To evaluate the impact of noninvasive functional mapping on decision-making and resection of eloquently located CCM. METHODS: Of 126 patients with intracranial cavernomas, we prospectively included 40 consecutive patients (31.7%) with highly eloquent CCM between 2012 and 2020. We performed functional mapping via navigated transcranial magnetic stimulation (nTMS) motor mapping in 30 cases and nTMS language mapping in 20 cases. Twenty patients suffered from CRE. CCM caused ICH in 18 cases. RESULTS: We used functional mapping data including function-based tractography in all cases. Indication toward (31 cases) or against (9 cases) CCM resection was influenced by noninvasive functional mapping in 36 cases (90%). We resected CCMs in 24 cases, and 7 patients refused the recommendation for surgery. In 19 and 4 cases, we used additional intraoperative neuromonitoring and awake craniotomy, respectively. Patients suffered from transient postoperative motor or language deficits in 2 and 2 cases, respectively. No patient suffered from permanent deficits. After 1 yr of follow-up, anti-epileptic drugs could be discontinued in all patients who underwent surgery but 1 patient. CONCLUSION: Surgery-related deficit rates are low even for highly eloquent CCM and seizure outcome is excellent. The present results show that noninvasive functional mapping and function-based tractography is a useful tool for the decision-making process and during microsurgical resection of eloquently located CCM.